Cortical Thickness Predicts Response Following 2 Weeks of SSRI Regimen in First-Episode, Drug-Naive Major Depressive Disorder: An MRI Study - Wu, Peiyi; Zhang, Aixia; Sun, Ning; Lei, Lei; Liu, Penghong; Wang, Yikun; Li, Hejun; Yang, Chunxia; Zhang, Kerang (Frontiers in Psychiatry, 2022)
Objective: Major depression disorder (MDD) is a harmful disease, and the pathological mechanism remains unclear. The primary pharmacotherapy regimen for MDD is selective serotonin reuptake inhibitors (SSRIs), but less than 40% of patients with MDD are in remission following initial treatment. Neuroimaging biomarkers of treatment efficacy can be used to guide personalized treatment in MDD. This study aims to determine if cortical thickness (CT) can be used as a predictor for SSRIs. Methods: A total of 126 first-episode, drug-naive MDD patients (MDDs) and 71 healthy controls (HCs) were enrolled in our study. Demographic data were collected according to the self-made case report form (CRF) at the baseline of all subjects. MRI scanning was performed, and all imaging was processed using the DPABISurf software. All MDDs were treated with SSRIs, and symptoms were assessed at both the baseline and 2nd week using the 17-item Hamilton Rating Scale (HAMD-17). According to the reduction rate of HAMD-17 ≤ 20% and HAMD-17 ≥ 50%, the MDDs were divided into the responders group and non-responders group. The receiver operating characteristic curve (ROC) was used to analyze the diagnostic value of MDDs and HCs CT for MDD. Correlation analysis was performed to identify the relationship between CT and SSRIs treatment efficacy in MDDs. Results: Significant decreases were found in the CT of the right supplementary motor area (SMA) in MDDs at the baseline (corrected by the Monte Carlo permutation correction, cluster-wise significant threshold at p<0.025 and vertex-wise threshold at p = 0.001), AUC=0.732 (95% CI=0.233-0.399). In the responders group, the CT of the right SMA was significantly thinner than in the non-responders group. There was a significant negative correlation (r=-0.629, p<0.0001) between the CT of SMA and HAMD-17 reductive rate (2w). Conclusion: Lower CT of the right SMA in MDD patients at the baseline may be a neuroimaging biomarker for MDD diagnosis, and a greater extent of thinner CT in the right SMA may predict improved SSRIs treatment response. Our study shows the potential of CT as a possible biomarker that predicts a patient’s clinical treatment response to SSRIs in MDD.